Exploring code switching in Malaysian political blogs - Mohd Fadli bin Zakaria (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
Code switching phenomenon has been present in multilingual societies (in this case; Malaysia) where languages, dialects and different varieties of the same language are used. Code switching has typically been attached with speaking. Conceptually, code switch in writing will not be any different from code switching in speaking due to the functions that both play. Furthermore, compared with other traditional media, the Internet is where more instances of code switching and language mixing can be found (Androutsopoulos, 2001). There are few detailed studies conducted on Bahasa Melayu-English code switching as it specifically pertains to, and there are even less studies conducted about Bahasa Melayu-English code switching in blogs. This study seeks to investigate (i) the frequency of code switching types used in Malaysian political blogs and (ii) the functions of code switching in Malaysian blogs. By applying Muysken's (2000) theoretical framework on categories of code switching, (i) insertion, (ii) alternation and (iii) congruent lexicalisation, data were compiled for this research. Entries from 50 political blogs were compiled and every code switched-word that occurred in the entries was tallied, labelled and calculated. The findings showed that basically Malaysian political bloggers do not code switch frequently in their writings. This may happen due to the theme they were writing; politics. The tone used to write about political issues is usually formal and sharp, and code switch rarely occurs in these formal settings.